Analisis Technologi Acceptance Model Dan Friend Workplace Terhadap Kinerja Karyawan - Deni Widyo Prasetyo (Fakultas Ekonomi Universitas Yos Soedarso, 2020)
Human Resource Management Issues have recently been discussed and positions have become very important in terms of employee performance. Employee performance is very important in the company. For this reason, the authors are interested in conducting research and compiling the results of this study with the title Analysis of Technologi Acceptance Model and Friend Workplace to Improve Employee Performance. From the description above, the formulation of the problems raised in this study are : 1. Is there a significant relationship between Technologi Acceptance Model on employee performance 2. Is there a significant relationship between Friend workplace on employee the performance objectives of this study are:To know the relationship between Technologi Acceptance Model to employee performance To find out the relationship between Friend workplace on employee performance Data collection techniques in this study using quantitative techniques is the analysis of data that has been given a score in accordance with the measurement scale. That has been applied to give meaning. For the hypothesis used multiple linear regression analysis with the following formula : The steps to do the regression between the independent variable and the dependent variable are as follows: regression dependent variable Employee Performance (Y) with the independent variable Technologi Acceptance Model (X1) dependent variable Employee Performance (Y) with the independent variable Friend workplace (X2) Keywords: Employee Performance, Technologi Acceptance Model, Friend workplace